Biochemical characterization of staphylococci isolated from rabbits (2002)
Coagulase activities of rabbit strains of staphylococci were tested using sterile human, rabbit and goat plasmas. Human plasma produced the most satisfactory coagulase sensitivity while the rabbit plasma was least sensitive. Human plasma tube coagulase gave a positive reaction within one hour, whereas rabbit and goat tube coagulase tests took two hours to complete. All 108 isolates of Staphylococcus aureus from clinically healthy rabbits fermented glucose, mannitol, sucrose, dulcitol and sorbitol, 98.1% fermented maltose and trehalose; 89.8% fermented lactose while only 46.3% fermented xylose. Urease activity was also high among the rabbit strains of staphylococci investigated.